(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
This study evaluated the effects of sugar and salt levels on the physicochemical properties and sensory attributes of crispy dried chicken meat and determined the optimal formulation. A 3 x 3 factorial design was applied using three salt levels (1.5, 3.0, and 4.5%) and three sugar levels (1.5, 3.0, and 4.5%). Data were analyzed using analysis of variance, and principal component analysis was used to integrate physicochemical and sensory parameters for formulation optimization. Increasing salt and sugar levels significantly reduced moisture content (1.67–1.85%) and water activity (0.49–0.54), while hardness increased from 4.60 to 5.73 N, contributing to the development of a crispy texture. Sensory evaluation showed that the formulation containing 1.5% salt and 3.0% sugar achieved the highest scores for colour, aroma, taste, and texture. Principal component analysis explained 93.4% of the total variance, revealing strong positive correlations among sensory attributes, whereas hardness was negatively associated with overall acceptability. The optimal formulation (1.5% salt and 3.0% sugar) provided a balance between product stability, texture, and sensory quality. These findings demonstrate that moderate sugar-salt levels are critical for optimizing crispy dried chicken meat and provide a scientific basis for further product development.